1987
DOI: 10.1111/j.1471-0528.1987.tb03105.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hirsutism in polycystic ovary syndrome with bromocriptine

Abstract: Summary The value of bromocriptine in the treatment of hirsutism in polycystic ovary syndrome (PCO) was assessed subjectively and photographically in a double‐blind trial in 22 women studied for 1 year. Menstrual frequency was recorded. Circulating concentrations of oestradiol, oestrone, testosterone, androstenedione, and sex hormone binding globulin (SHBG) were determined before treatment and after 6 and 12 months therapy. On the same occasions gonadotrophin concentrations (mean of 24 samples) and their respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Clinical data do not support a therapeutic role for BRC in the treatment of hyperandrogénie signs (hirsutism and acne) or menstrual regulation in PCO, confirming the data of Murdoch et al [25] and in opposition to those of Spruce et al [26] who found an improvement in men strual frequency.…”
Section: Discussioncontrasting
confidence: 47%
“…Clinical data do not support a therapeutic role for BRC in the treatment of hyperandrogénie signs (hirsutism and acne) or menstrual regulation in PCO, confirming the data of Murdoch et al [25] and in opposition to those of Spruce et al [26] who found an improvement in men strual frequency.…”
Section: Discussioncontrasting
confidence: 47%
“…Bromocriptine is not therapeutic for hirsutism in PCOS (137). The antiestrogen agent clomiphene citrate is also not useful in the management of the cutaneous manifestations of PCOS.…”
Section: Treatment Of Skin Manifestationsmentioning
confidence: 99%
“…However, bromocriptine, a dopamine agonist, has little or no effect on gonadotropins in women with PCOS. 41,42 Reduced hypothalamic opioid tone was implicated in the etiology of elevated LH. Initial studies in which naloxone, an opioid receptor blocker, was infused showed a lack of LH increase in women with PCOS.…”
Section: Potential Mechanisms Of Altered Gonadotropin Secretionmentioning
confidence: 99%